EVALUASI EFEKTIVITAS PROGRAM DINAS TENAGA KERJA DAN TRANSMIGRASI DALAM MENINGKATKAN KUALITAS TENAGA KERJA DI KABUPATEN SUMBAWA - Elly Karmeli; Wahyu Haryadi; Nita Wulandari (Pusat Riset dan Publikasi, 2025)
This study aims to evaluate the effectiveness of the Manpower and Transmigration Department program in improving the quality of the workforce in Sumbawa District. The type of this study was descriptif. The type of data used in this study was quantitative and qualitative data. Quantitative data in the form of the initial and final number of participants in the training program, while qualitative data in the form of explanations from research informants regarding the implementation of the training program organized by the Manpower and Transmigration Department of Sumbawa District. The collected of data was analyzed using effectiveness analysis techniques. Based on the data analysis, it can be concluded that the implementation of the workforce quality improvement program by the Sumbawa Regency Manpower and Transmigration Office over the past five years has been categorized as less effective. The program's implementation, from planning and preparation to execution, has not been carried out optimally, resulting in the failure to achieve the final results according to the set targets or objectives. Therefore, ongoing efforts to improve these various programs are essential to ensure they continue to adapt to developments in the business world and the increasingly dynamic needs of the job market.